2012
DOI: 10.1007/s00330-012-2428-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of MR perfusion imaging using blood pool contrast agent in subjects without pulmonary diseases and in patients with pulmonary embolism

Abstract: • Recently introduced blood pool contrast agents improve MR evaluation of lung perfusion • Regional differences in lung perfusion indicating a gravitational and isogravitational dependency. • Focal areas of significantly decreased perfusion are detectable in pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…In accordance with previous studies, PBF, PBV, SI and upslope in the posterior dependent lung were significantly higher than in the anterior non-dependent lung and, inversely, MTT was significantly shorter in the posterior than in the anterior lung parenchyma [7, 8, 33]. For example, by MRI measurement Ohno et al found comparable significant regional PBF differences of 148.1±17.3 ml blood per min and 100ml lung in the posterior and 97.6±13.7 ml blood per min and 100ml lung in the anterior lung parenchyma [8].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with previous studies, PBF, PBV, SI and upslope in the posterior dependent lung were significantly higher than in the anterior non-dependent lung and, inversely, MTT was significantly shorter in the posterior than in the anterior lung parenchyma [7, 8, 33]. For example, by MRI measurement Ohno et al found comparable significant regional PBF differences of 148.1±17.3 ml blood per min and 100ml lung in the posterior and 97.6±13.7 ml blood per min and 100ml lung in the anterior lung parenchyma [8].…”
Section: Discussionsupporting
confidence: 92%
“…Absolute quantification of pulmonary parenchymal perfusion is challenging and time-consuming and requires specific imaging and contrast protocols as well as dedicated post-processing software [21, 33]. A close correlation between quantitative and semi-quantitative MRI parameters of pulmonary perfusion was observed in this study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Flow partly depends on the three dimensional anatomy of the pulmonary arteries and obstructing clots, which is available from CT or magnetic resonance imaging, and the distal capillary resistance. Our analysis depends on knowing left and right selective pulmonary artery blood flow which is currently only available via magnetic resonance imaging(MRI) [15]. Knowledge of the left and right pulmonary artery flows enables the contribution from each lung to be assessed, as well as being vital for the calculation on the overall effect of thromboendarterectomy.…”
Section: Discussionmentioning
confidence: 99%